Metal‐Free Synthesis of Fluorinated Indoles Enabled by Oxidative Dearomatization. (8th January 2016) - Vitaku, Edon; Smith, David T.; Njardarson, Jon T.
Abstract: Nitrogen heterocycles are found in a majority of approved small‐molecule pharmaceuticals, and the number of approved fluorinated drugs is increasing each decade. Therefore, new approaches for accessing fluorinated nitrogen heterocycles are of great significance. A novel, scalable, and metal‐free method for accessing a wide range of fluorinated indoles is described. This oxidative‐dearomatization‐enabled approach assembles 2‐trifluoromethyl NH‐indole products from simple commercially available anilines with hexafluoroacetylacetone in the presence of an organic oxidant. The nature of the aniline N‐capping group is critical for the success of this new reaction. Furthermore, the indole products contain a 3‐trifluoroacetyl group, which can be exploited to access a plethora of useful functional groups.